Pengaruh Variasi Waktu Pemeraman Terhadap Nilai Uji Kuat Tekan Bebas pada Tanah Lempung dan Lanau yang Distabilisasi Menggunakan Kapur pada Kondisi Rendaman - A., Putra Andrean; Iswan, Iswan; Jafri, Muhammad (Universitas Lampung, 2016)
Clay And Silt Soil Is A Kind Of Soil That Has A Bad Soil Bearing Capacity. One Of SoilImprovements That We Can Do Is Use A Mixture Of Hydrated Lime. In Addition To MoreEconomical Reason, It Also Has Good Ability In The Soil Stabilization With Fine Grain Soil.The Clay Soil Sample Is A Type Of High Plasticity Clay That Taken From Rawa Sragi- Jabung-East Lampung District And Then The Silt Soil Sample Is Taken From Yosumulyo-East Metro-Metro City. Based On Previous Experiments, That Soil Is Included In Soft Clay And HighPlasticity Category Which Has High Plasticity Index Value >11%. Based On Unified SoilClasification (Uscs), Clay Belong To Cl Category, While Silt Soil Belong To Cl-Ml Category. InModified Proctor Compact Test Result, Adding Hydrated lime Prove To Reduce Maximum DensityValue (Γd), And For Optimum Water Content (Ω opt ) Having An Increaces But Not Significant. InUnconfined Compressive Strength Test, Clay And Silt Soil With Variation Of Curing Time AndSoaked Condition, Soil With Hydrated Lime Mixtured With Modified Proctor Compacted, ForClay Soil, It Get Qu Optimum Value Increased When It Has 15% Hydrated Lime Content, 28 DaysOf Curing Time, It Get 0,3636 Kg/Cm2. For Silt Soil Qu Optimum Value Inscreased When It Has15% Hydrated Lime Content And 28 Days Of Curing Time, It Get 0,3411 Kg/Cm2. Hydrated LimeAdding Could Inscred Unconfined Compressive Strength But With Longer Curing Time Duration(28 Days) Because The Greater The Qu Soil Value, The Greater The Soil Bearing Capacity.Keywords: Hydrated Lime, Clay, Silt, Unconfined Compressive Strength, Soil Bearing Capacity